Avaliação produtiva e sanitária em bovinos confinados sob metafilaxia antimicrobiana - Baptista, Anderson Lopes (2017)
Bovine respiratory diseases (DRB) are multifactorial, affect productive and sanitary indices, and metaphylaxis is an alternative for DRB challenges in confinement. The aim of this study was to evaluate metaphylaxis with oxytetracycline and tildipirosin in these systems. In the retrospective study, 42,997 animals were used: control (n=20,763), oxytetracycline (n=11,896) and tildipirosin (n=10,338), being low, medium and high risk for DRB, respectively. In the second study, 1,780 uncastrated male Nellore cattle from 18 to 24 months old, mean weight of entry 366.9 ± 19.9 kg, which covered 657.9 ± 302.3 km and rested for 10.4 ± 15.6 days. They were divided in experiment 1 (n=1,780), control (n=628) and metaphylaxis (n=1,152) and 2 (n=1,152) animals divided into untreated (n=568) and treated (n=584). In the first study, the general morbidity was 7.26% with a difference (P<0.001) in the oxytetracycline protocol (8.36%) and control (6.75%) and tildipirosin (7.04%). Overall mortality was 0.06%, 0.03% in high-risk animals (tildipirosin), 0.04% in control (P=0.197) and 0.017% in oxytetracycline. The mean daily gain (ADG) increased by 1.21% (oxytetracycline) and 6.17% (tildipirosin) compared to those without metaphylaxis (P<0.001), and ADG was higher in healthy and tildipirosin patients. In the second study, the general morbidity of experiment 1 was 4.77%, 6.5% and 3.8% in the control and metaphylaxis groups (P=0.02), respectively. There were no DRB deaths. Among productive indexes, CDG (P = 0.002) and ADG (P=0.039) were higher in animals of the metaphylaxis group. In experiment 2, overall morbidity was 3.8%, 4.6% and 3.08% in the untreated and treated groups, respectively (P=0.6914). The mean final weight of the animals from the untreated group (532.30 ± 34.94 kg) presented a tendency (P=0.0579) to be lower than that of the treated group (535.40 ± 34.20 kg). The same was observed in the evaluation of ADG, but without difference (P=0.0558). Regarding CDG, there was no difference between the groups (P=0.3524). It was concluded that metaphylaxis with tildiprosin, performed in half of animals with high risk for respiratory diseases at the entrance of confinement, reduces morbidity and improves productive performance when compared to those without metaphylaxis.